Design and analysis of high performance matrix filling for DNA sequence alignment accelerator using asic design flow: article / Nurzaima Mahmod - Mahmod, Nurzaima
This paper presents the design and analysis high performance matrix filling for DNA sequence alignment accelerator using ASIC design flow. The objective of this paper is to design and analysis matrix module of DNA sequence alignment accelerator using clock cycle to get high performance. The scope of this paper is to optimize the DNA sequences alignment on the matrix rilling module by implementing a parallel method of the Smith-Waterman algorithm. This method provides magnificent speed up over than traditional sequential implementation methods while it sensitivity detection is still remained. To optimize the performance of the algorithm by exploiting parallelism in the design several techniques have been developed. In the advanced engineering technology, the massive parallelism can be implemented by using the Field Programmable Logic Array (FPGA) techniques. The design was developed in Verilog HDL coding and synthesis by using LINUX tools. From the LINUX tools, the optimum combination of parameten is manipulated to produce the most energy efficient IC. The design produces an ASIC that can work at 5ns until tons clock period and range of ICC time between 0.63ns until l.67ns. The area of this design is 10304.358mm2